PREDIKSI RETURN PORTOFOLIO MENGGUNAKAN METODE KALMAN FILTER - Dita Rosita Sari; Tatik Widiharih; Sugito Sugito (Jurnal Gaussian, 2016)
Stock is an evidence for individual or institutional ownership about a company. To cover losses in stocks investment, should be done diversification to spread  risk in some stocks called as portfolio. Portfolio is a joint of two or more stocks investment that are choosen as investment’s targets over spesific time periods and certain rules. To minimize losses in stocks investment, needed to predict portfolio return for some coming periods. Good prediction has small difference with actual data. One method that can minimize MSE is Kalman Filter. Kalman Filter estimates a process through feed back Control Mechanism called recursion. The variable used are monthly portfolio return of PT Mayora Indah Tbk and PT Indofood Sukses Makmur Tbk in January 2005 until December 2015. Data In January 2005 until December 2014 are used to predict the return portfolio for Year 2015. After that, an interval is made for those forecast results and compare with actual data. If actual data are residing in the interval, then Kalman Filter method can be used to predict portfolio return for year 2016. The MSE value with kalman Filter is 0,00225 and the MSE value with Box-Jenkis method is 0,00253, so Kalman Filter can minimize the MSE value. Keywords : portfolio return, Box-Jenkins, Kalman Filter